Perinatal Outcome in Patients of Antepartum Haemorrhage - Bakhtawar Dahri, Iram Taj, Aisha Taj, Tuba Nadeem, Karamun Nisa (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To determine the perinatal outcome in patients of antepartum haemorrhage at tertiary care hospital. Study design: descriptive, case series. Settings: Department of Gynecology & Obstetrics, Liaquat National Hospital Karachi. Study duration: 3rd November 2018 to 2nd May 2019. Materials & Methods: Total 132 patients with antepartum haemorrhage of 15-45 years of age were selected. Congenital anomalies detected on ultrasonography were excluded. A detailed history including patient’s age, parity, gestational age, and presenting complaints was taken. A general examination with recording of vital signs was performed followed by systemic examination. All parameters of maternal and fetal well-being were recorded. All cases with antepartum haemorrhage were evaluated and perinatal outcome of patients with antepartum haemorrhage was recorded including low birth weight, still birth and neonatal death. Results: Age range in this study was from 15 to 45 years with mean age of 28.94 ± 4.23 years. Majority of the patients 79 (59.85%) were between 15 to 30 years of age. Mean gestational age was 33.20 ± 3.92 weeks. Mean parity was 3.13 ± 0.89. Mean amount of bleeding per vagina was 845.33 ± 67.22 ml. In this study, frequency of perinatal outcome in patients of antepartum haemorrhage was as follows; low birth weight was found in 71 (53.79%), stillborn in 56 (42.42%) patients and neonatal death in 23 (17.42%) patients. Conclusion: This study concluded that a proper protocol should be designed in these high risk patients for antenatal monitoring and proper management plans in order to reduce the morbidity and mortality of the fetus. Keywords: Antepartum Haemorrhage, Low Birth Weight, Neonatal Death.